Experts' Opinion Matters! Green Technology Elements for Construction Technology in Vocational Colleges - Kaliappan, Anusuya; Hamid, Hashima; Madar, Ahmad Rizal (uthm, 2023)
Green Technology refers to clean energy production, the use of alternative fuels, and technologies that are less harmful to the environment than fossil fuels. It has garnered a significant amount of interest due to increasing awareness about the impacts of climate change and the depletion of natural resources. While the buildings emit more carbon dioxide and other greenhouse gases than other industries, the use of Green Technology will be able to reduce human impacts on the natural environment and prevent climate change. Therefore, the purpose of this study is to investigate the Green Technology Elements for Construction Technology in Vocational College that is seen fundamental as these students will be in the construction workforce in the future. The study was conducted using the Fuzzy Delphi Method (FDM) involving a combination of 20 experts with various expertise from a heterogeneous group. A set of questionnaires using a 7-point Likert Scale was formed based on expert interviews in the first phase of this study and the data obtained were then analysed using triangular fuzzy numbers and ranking for each variable was determined using the defuzzification process. The findings showed that all elements listed reached the experts' consensus. Expert consensus also found that the Carbon Initiatives element ranked first meanwhile the Introduction to Green Technology element ranked last in the list of elements. These elements are agreed upon in preparing academically exemplary individuals while ensuring every graduate from Vocational College, especially from the Construction Technology course is equipped with job-ready skills to tackle real-life problems.